Late-onset palsy of the recurrent laryngeal nerve after thyroid surgery. Issue 12 (16th September 2014) - Bures, C; Bobak-Wieser, R; Koppitsch, C; Klatte, T; Zielinski, V; Freissmuth, M; Friedrich, G; Repasi, R; Hermann, M
Abstract: Background: A small subset of patients may develop late-onset palsy of the recurrent laryngeal nerve (RLN) after thyroid surgery. However, no conclusive data have been published regarding the incidence of, and possible risk factors for, this complication. Methods: Preoperative, intraoperative and postoperative data from consecutive patients who underwent thyroid surgery at a single centre between 1999 and 2012 were analysed. Late-onset palsy of the RLN was defined as deterioration of RLN function after normal vocal cord function as investigated by routine preoperative and postoperative laryngoscopy. Results: The cohort included 16 692 patients with 28 757 nerves at risk. Early postoperative palsy of the RLN was diagnosed in 1183 nerves at risk (4·1 per cent), whereas late-onset RLN palsy was found in 41 (0·1 per cent). Late-onset palsy of the RLN was diagnosed after a median interval of 2·5 (range 0·5–12) weeks and nerve function recovered completely in 28 patients after a median interval of 3 months. This recovery rate was significantly lower than that for early-onset RLN palsy: 1068 (90·3 per cent) of 1183 nerves ( P < 0·001). No particular risk factor for late-onset RLN palsy was identified. Conclusion: Late-onset palsy of the RLN was diagnosed in a small subset of patients after thyroid surgery, and recovery of nerve function occurred less frequently than in patients with early-onset RLN palsy. Abstract : Rare but real